2008
DOI: 10.1002/pros.20828
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular death platform steps‐in: Targeting prostate tumors via endoplasmic reticulum (ER) apoptosis

Abstract: Molecular targeting of apoptotic signaling pathways has been extensively studied in recent years and directed towards the development of effective therapeutic modalities for treating advanced androgenindependent prostate tumors. The majority of therapeutic agents act through intrinsic or mitochondrial pathways to induce programmed cell death. The induction of apoptosis through endoplasmic reticulum (ER) stress pathways may provide an alternative to treat patients. The functional interaction between the BCL-2 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…Recently, ER stress-induced cancer cell apoptosis has become a novel signaling target for the development of cancer therapeutic drugs [ 22 24 ]. Various pathological conditions, such as hypoxia, ER-Ca2 + depletion, oxidative injury, hypoglycemia and viral infections, may cause an imbalance between the protein folding load and capacity; this cellular condition is known as ER stress [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ER stress-induced cancer cell apoptosis has become a novel signaling target for the development of cancer therapeutic drugs [ 22 24 ]. Various pathological conditions, such as hypoxia, ER-Ca2 + depletion, oxidative injury, hypoglycemia and viral infections, may cause an imbalance between the protein folding load and capacity; this cellular condition is known as ER stress [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially significant, since apoptosis due to ERS recently emerged as a strategy for PC treatment. 45,46 The comparison of cytostatic and cytotoxic effects of BZ combinations with FA or CpdA revealed superior potency of CpdA+BZ regimen. Glucocorticoids are known to induce expression of anti-apoptotic and self-defense genes and to desensitize cells against apoptosis by GR.…”
Section: Discussionmentioning
confidence: 99%
“…it has been suggested that depletion of Ca 2ϩ from ER invokes a number of secondary events like the unfolded protein response (UPR) (2)(3)(4)(5) and activation of store-operated Ca 2ϩ entry (SOCE), flooding the cells with extracellular Ca 2ϩ (6 -8). Eventually, these events are considered to trigger cell death either by cytotoxicity arising from prolonged elevations of [Ca 2ϩ ] i (9 -11) or a stress situation created by Ca 2ϩ depletion from ER, leading to caspase activation and apoptosis (2)(3)(4)(5). However, there is no consensus about the relative importance of these events for the apoptosis induced by Tg: whether it is Ca 2ϩ depletion of ER or an increase in [Ca 2ϩ ] i that is decisive or whether both factors may, in fact, be important for an apoptotic outcome.…”
mentioning
confidence: 99%